Odpowiedzi

2009-12-11T15:58:30+01:00
B ) 1-4( x + 2 )² = ( 1 - 2x ) ( 1+ 2x )
1-4(x²+4x+4)=1-4x
1-4x²-16x-16=1-4x²
-4x²-16x+4x²=1-1+16
-16x=16/:(-16)
x=-1

a ) ( 3x-4 )² + 4( 2x+1 )² = ( 5x + 2 ) ( 5x- 2 )
9x²-24x+16+4(4x²+4x+1)=25x²-4
9x²-24x+16+16x²+16x+4=25x²-4
9x²-24x+16x²+16x-25x²=-4-16-4
-8x=-24/:(-8)
x=3
mam nadzieje ze pomogłam tam sie w tych zadaniach skraca
Najlepsza Odpowiedź!
2009-12-11T16:02:02+01:00
A) ( 3x-4 )² + 4( 2x+1 )² = ( 5x + 2 ) ( 5x- 2 )
9x²-24x+16+4(4x²+4x+1)= 25x²-10x+10x-4
9x²-24x+16+16x²+16x+4=25x²-4
-24x+16x=-4-16-4
-8x=-24 / :8
x=3

b) 1-4( x + 2 )² = ( 1 - 2x ) ( 1+ 2x )
1-4(x²+4x+4)=1+2x-2x-4x²
1-4x²-16x-16=1-4x²
-16x=1-1+16
-16x=16 / :(-16)
x=-1

2009-12-11T16:02:31+01:00
A)
(3x-4)(3x-4) + 4 (2x+1)(2x+1) = (5x+2) ( 5x - 2 )
9x² -12x -12x + 16 + 4x² + 2x + 2x + 1 = 25x - 4
13x² - 45x = -21 <- według mnie inaczej wyjść nie może

wzór skróconego mnożenia
( a+b )² = ( a +b ) ( a + b ) = a² + ab + ab + b² = a² + 2 ab + b²

b)
1-4 (x + 2)(x + 2) = ( 1-2x)(1+2x)
1-4 (x² + 2x + 2x+4) = 1 + 2x - 2x + 4x
1-4 (x² + 4x + 4) = 1 + 4x
-3x² = -4+1
-3x² = 3 / :3
x² = 1
x = -1